Structural constraints of functional connectivity drive cognitive impairment in the early stages of multiple sclerosis. (April 2021) - Koubiyr, Ismail; Deloire, Mathilde; Brochet, Bruno; Besson, Pierre; Charré-Morin, Julie; Saubusse, Aurore; Tourdias, Thomas; Ruet, Aurélie
Background: The relationship between structural and functional deficits in multiple sclerosis (MS) is unclear. Objective: This study explored structure-function relationships during the 5 years following a clinically isolated syndrome and their role in cognitive performance. Methods: Thirty-two patients were enrolled after their first neurological episode suggestive of MS and followed for 5 years, along with 10 matched healthy controls. We assessed structural (using diffusion tensor imaging) and functional (using resting-state functional magnetic resonance imaging (fMRI)) brain network metrics, clinical and cognitive scores at each follow-up visit. Structural–functional coupling, calculated as the correlation coefficient between strengths of structural and functional networks, was used to assess structure–function relationships. Results: Structural clustering coefficient was significantly increased after 5 years, whereas characteristic path length decreased. Structural connections decreased after 1 year and increased after 5 years. Functional connections and related path lengths were decreased after 5 years. Structural–functional coupling had increased significantly after 5 years. This structural–functional coupling was associated with cognitive and clinical evolution, with stronger coupling associated with a decline in both domains. Conclusion: Our findings provide novel biological evidence that MS leads to a more constrained anatomical-dependant functional connectivity. The collapse of this network seems to lead to both cognitive worsening and clinical disability.